2018
DOI: 10.1016/s0140-6736(18)31613-1
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous remifentanil patient-controlled analgesia versus intramuscular pethidine for pain relief in labour (RESPITE): an open-label, multicentre, randomised controlled trial

Abstract: National Institute for Health Research Clinician Scientist Award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 21 publications
4
41
0
Order By: Relevance
“…Today, there is evidence that pain relief with remifentanil PCA is effective; less effective than neuraxial analgesia, but more effective than long‐acting opioids or nitrous oxide . In view of the high maternal satisfaction rate of the remifentanil group in Wilson et al's study , complete labour pain relief may not be the ultimate goal. Good midwifery care might be equally or more important .…”
Section: Confusing Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Today, there is evidence that pain relief with remifentanil PCA is effective; less effective than neuraxial analgesia, but more effective than long‐acting opioids or nitrous oxide . In view of the high maternal satisfaction rate of the remifentanil group in Wilson et al's study , complete labour pain relief may not be the ultimate goal. Good midwifery care might be equally or more important .…”
Section: Confusing Recommendationsmentioning
confidence: 99%
“…If pethidine was replaced by remifentanil PCA in UK labour wards, approximately 27,000 women per year would not be exposed to the long‐term risks of instrumental deliveries. This has to be weighed against the approximately 250,000 women per year that would be exposed to a short‐term respiratory risk (extrapolated from ). Several anaesthetic units in the UK have demonstrated that routine use of remifentanil PCA strengthens the skills and reduces the risk of severe respiratory depression .…”
Section: Confusing Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of pethidine analogs were synthesized and their affinities for the [ 3 H]N-methyl-scopolamine (NMS) binding site on muscarinic acetylcholine receptors were determined [6]. Pethidine has been also used to relieve labor pain [7]. Also, a method for the quantitative determination of pethidine (meperidine) and its metabolic norpethidine (normeperidine) in human hair by LC-MS-MS has been proposed [8].…”
Section: Introductionmentioning
confidence: 99%